Medication in the elderly : an outpatient survey - Davis, Christopher Karl (Division of Geriatric Medicine, 2018)
The aging process is associated with disease states that may be painful, disabling and life-threatening. Elderly patients frequently have more than one disorder and appropriate pharmacotherapy may result in polypharmacy (treatment with multiple drugs). This situation, combined with age-related alterations in the handling of and sensitivity to drugs, predisposes older patients to adverse drug reactions (ADR's). This study was undertaken to assess the actual risks and potential benefits of long-term polypharmacy in the management of elderly hospital out-patients. A particular aim was to get some indication of whether or not polypharmacy was justifiable in the study population. Accordingly, the medical records of 132 ambulatory patients, 70 years of age and over, who had been attending the general out-patient department of a large teaching hospital for a period of twelve months or longer, were retrospectively examined. The patient's age, diagnoses, prescribed medication, ADR's and clinical therapeutic benefit were assessed, recorded and analyzed. The average patient age in the sample studied was 77,6 years. 71% of the sample were females. 419 disorders were identified, giving an average of 3,17 per patient. 603 drugs were prescribed in total, giving an average of 4, 57 per patient. There was no statistically significant association between increasing age and the number of diagnoses per patient or the number of drugs prescribed. Medication was felt to be therapeutically effective in 63% of the patients, whilst an ADR was noted in 14% of the sample. There was no statistically significant difference in the age, number of diseases or number of drugs prescribed between the total group, the ADR group and the non-ADR group. These parameters were therefore not useful in identifying those patients more likely to experience an ADR. The apparent effectiveness of the medication prescribed and the relatively low incidence of ADR' s in the group studied suggests that appropriate and judicious multiple drug therapy can benefit many elderly ambulatory patients and therefore polypharmacy could be regarded as permissible in this context. Apart from these observations, this dissertation also includes recommendations on ways to minimize the incidence of ADRs in the elderly, and areas for ongoing research in this field are identified.